Skin microvascular endothelial dysfunction is associated with type 2 diabetes independently of microalbuminuria and arterial stiffness. (July 2017) - Jonasson, Hanna; Bergstrand, Sara; Nystrom, Fredrik H; Länne, Toste; Östgren, Carl Johan; Bjarnegård, Niclas; Fredriksson, Ingemar; Larsson, Marcus; Strömberg, Tomas
Skin and kidney microvascular functions may be affected independently in diabetes mellitus. We investigated skin microcirculatory function in 79 subjects with diabetes type 2, where 41 had microalbuminuria and 38 not, and in 41 age-matched controls. The oxygen saturation, fraction of red blood cells and speed-resolved microcirculatory perfusion (% red blood cells × mm/s) divided into three speed regions: 0–1, 1–10 and above 10 mm/s, were assessed during baseline and after local heating of the foot with a new device integrating diffuse reflectance spectroscopy and laser Doppler flowmetry. Arterial stiffness was assessed as carotid-femoral pulse wave velocity. Subjects with diabetes and microalbuminuria had significantly higher carotid-femoral pulse wave velocity compared to subjects without microalbuminuria and to controls. The perfusion for speeds 0–1 mm/s and red blood cell tissue fraction were reduced in subjects with diabetes at baseline and after heating, independent of microalbuminuria. These parameters were correlated to HbA1c. In conclusion, the reduced nutritive perfusion and red blood cell tissue fraction in type 2 diabetes were related to long-term glucose control but independent of microvascular changes in the kidneys and large-vessel stiffness. This may be due to different pathogenic pathways in the development of nephropathy, large-vessel stiffness and cutaneous microvascular impairment.